The Influence of Social Cohesion Oncommunity Preparedness in the Face of Tsunami Disaster in Pasiripis Village, Surade Sub District, Sukabumi District - Budhiana, Johan (STIKep PPNI Jawa Barat, 2024)
Aims: This study was to determine the effect of social cohesion on community preparedness for tsunami disaster in Pasiripis Village, Surade Subdistrict, Sukabumi Regency. Methods: This type of research is correlational with cross sectional approach. The population was all people in Pasiripis Village, Surade Sub-district, Sukabumi District and the sample was 160 people using purposive sampling technique. Data collection techniques using questionnaires. Data analysis used univariate analysis with frequency distribution table, bivariate analysis with simple linear regression, and multivariate analysis with multiple linear regression. Results: There is a significant influence of psychological sense of community, neighboring, and attraction on community preparedness in facing tsunami disaster (p < 0.05). There is a simultaneous influence of psychological sense of community, neighboring, and attraction on community preparedness in facing tsunami disasters (p < 0.05). Conclusion: There is an influence of psychological sense of community, neighboring, and attraction on community preparedness in facing tsunami disaster in Pasiripis Village, Surade Subdistrict, Sukabumi Regency. There is a simultaneous influence of psychological sense of community, neighboring, and attraction on community preparedness in facing tsunami disaster in Pasiripis Village, Surade Subdistrict, Sukabumi Regency.